Evaluation of a problem-solving (PS) techniques-based intervention for informal carers of patients with dementia receiving in-home care. (23rd January 2015) - Chiu, Mary; Pauley, Tim; Wesson, Virginia; Pushpakumar, Dunstan; Sadavoy, Joel
ABSTRACT: Background: The value of care provided by informal carers in Canada is estimated at 26 billion annually (Hollander et al., 2009). However, carers' needs are often overlooked, limiting their capacity to provide care. Problem-solving therapy (PST), a structured approach to problem solving (PS) and a core principle of the Reitman Centre CARERS Program, has been shown to alleviate emotional distress and improve carers' competence (Chiu et al., 2013). This study evaluated the effectiveness of problem-solving techniques-based intervention based on adapted PST methods, in enhancing carers' physical and emotional capacity to care for relatives with dementia living in the community. Methods: 56 carers were equally allocated to a problem-solving techniques-based intervention group or a control arm. Carers in the intervention group received three 1 hr visits by a care coordinator (CC) who had been given advanced training in PS techniques-based intervention. Coping, mastery, competence, burden, and perceived stress of the carers were evaluated at baseline and post-intervention using standardized assessment tools. An intention-to-treat analysis utilizing repeated measures ANOVA was performed on the data. Results: Post-intervention measures completion rate was 82% and 92% for the intervention and control groups, respectively. Carers in the intervention group showed significantly improved task-oriented coping, mastery, and competence and significantly reduced emotion-oriented coping, burden and stress ( p < 0.01–0.001). Control carers showed no change. Conclusion: PS techniques, when learned and delivered by CCs as a tool to coach carers in their day-to-day caregiving, improves carers' caregiving competence, coping, burden, and perceived stress. This may reduce dependence on primary, psychiatric, and institutional care. Results provide evidence that establishing effective partnerships between inter-professional clinicians in academic clinical health science centers, and community agencies can extend the reach of the expertise of specialized health care institutions.